Effectiveness of smartphone application in increasing knowledge on COPD and its non-pharmacological management in COPD patients - Adida, Fiony; Pandia, Pandiaman; Pradana, Andika; Tarigan, Amira P.; Ashar, Taufik; Dangana, Amos; Listyoko, Aditya S. (Narra J, 2023)
Chronic obstructive pulmonary disease (COPD) is among top ten of the world's causes of death. The development of the “Paru Sehat” smartphone application is a positive initiative and might have the potential to improve the disease management of COPD, improve patient’s quality of life, and reduce complications associated with COPD. However, its effectiveness in improving the knowledge of the COPD patients is unknown. The aim of this study was to determine the effectiveness of “Paru Sehat” in increasing knowledge on COPD and its non-pharmacological management in COPD patients. A quasi-experimental study with a one-group pretest-posttest was conducted among stable COPD patients at Prof. Chairuddin Panusunan Lubis Hospital, Medan, Indonesia. Bristol COPD knowledge questionnaire (BCKQ) was used to assess the knowledge scores of the patients before and after exposure to the “Paru Sehat” twice a week for four weeks. A dependent Student t-test was used to compare the knowledge scores between pre- and post-intervention for both knowledge domains (i.e., knowledge on the disease and non-pharmacological management). Student t-test or one-way ANOVA were used to determine the association between patients’ characteristics and the knowledge scores within pre- and post-treatment. Our data indicated a significant improvement of the knowledge scores on disease between pre- and post-treatment (15.92±3.79 vs 19.56±3.68, p<0.001). The knowledge score on non-pharmacological management also increased significantly post-treatment (7.52±2.02) compared to pre-treatment (10.08±2.379), p<0.001. In addition, this study found that educational attainment was associated with the scores of both knowledge domains of which individuals with senior high school or higher education level had significantly improvement of knowledge scores. This study highlights that although “Paru Sehat” application could improve the knowledge on COPD and its non-pharmacological management, its effects are less effective among individuals with low educational attainment.